2016
DOI: 10.3889/oamjms.2016.132
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Assessment of Moringa Oleifera Extracts and Its Incorporation in Novel Dental Remedies against Some Oral Pathogens

Abstract: AIM:To assess the antibacterial and antifungal potentials of different parts of Moringa oleifera plant using different extraction methods in attempts to formulate natural dental remedies from this plant.MATERIAL AND METHODS:Three solvents extracts (Ethanol, acetone, and ethyl acetate) of different parts of Egyptian Moringa tree were prepared and tested against oral pathogens: Staphylococcus aureus, Streptococcus mutans, and Candida albicans using disc diffusion method; As well as to incorporate the plant extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Natural herbalists use the different parts of MO, such as leaves, roots, flowers, fruit, and seeds, to obtain different extracts of Moringa. Among them, Moringa leaf extract is known for its rich contents of calcium, potassium, iron, phosphorous, and vitamins (vitamins A, D, C, E, ascorbic acid, and β-carotene), in addition to natural antioxidants and phytochemical flavonoids, such as polyphenol oxidase, oxidase, and catalase, which has great medicinal importance [20,[25][26][27]. Recent studies focused on the use of MO leaf meal in fish feeds as a cheap and locally available plant, with increasing protein contents [28].…”
Section: Introductionmentioning
confidence: 99%
“…Natural herbalists use the different parts of MO, such as leaves, roots, flowers, fruit, and seeds, to obtain different extracts of Moringa. Among them, Moringa leaf extract is known for its rich contents of calcium, potassium, iron, phosphorous, and vitamins (vitamins A, D, C, E, ascorbic acid, and β-carotene), in addition to natural antioxidants and phytochemical flavonoids, such as polyphenol oxidase, oxidase, and catalase, which has great medicinal importance [20,[25][26][27]. Recent studies focused on the use of MO leaf meal in fish feeds as a cheap and locally available plant, with increasing protein contents [28].…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of seeds from Moringa oleífera showed a potent cytotoxic activity, with reduction of cell viability of the cancer cell lines HeLa, HepG2, MCF-7, CACO-2 and L929 [13]. Microbial assays using seeds showed inhibition of the growth of the pathogenic bacteria Staphylococcus aureus e Streptococcus mutans [14].…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial tests with root extracts showed an antibacterial effect against the growth of Staphylococcus aureus and Streptococcus mutans [14], and from the pods inhibited Vibrio. vulnificus V. cholerae, V. mimicus and E. coli [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies examined the antimicrobial activity of the essential oil of Moringa oleifera against Pseudomonas aeruginosa, Bacillus cereus, Escherichia coli, Staphylococcus aureus and different fungal isolates Penicillium digitatum, Penicillium aurantiogriseum, Penicillium citrinum, Penicillium expansum and Aspergillus niger and found that all microorganisms tested were sensitive to the essential oil (Marrufo et al, 2013). Moreover, extracts of other parts of Moringa oleifera have been examined and control successfully bacterial growth of Streptococcus mutans and Staphylococcus aureus (Elgamily et al, 2016).…”
Section: Introductionmentioning
confidence: 99%